2016
DOI: 10.5350/dajpn2016290304
|View full text |Cite
|
Sign up to set email alerts
|

Determination of beliefs, attitudes of consulting teachers towards mental diseases, and referral reasons of their students to a child and adolescent psychiatrist

Abstract: Determination of beliefs, attitudes of consulting teachers towards mental diseases, and referral reasons of their students to a child and adolescent psychiatristObjective: In the present study, the aim was to evaluate the beliefs and attitudes of school counselors about mental illnesses, and reasons why counselors referred students to psychiatrists. Method:The study was carried out with 118 school counselors. Data were collected with sociodemographic information form and Beliefs toward Mental Illness Scale (BM… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(1 citation statement)
references
References 25 publications
0
1
0
Order By: Relevance
“…Studies have found that 10% of adolescents sought guidance from their teachers when faced with problems (Oban, 2011). Therefore, schools have become a consulting centers where students could get help safely (Kütük et al, 2016). Furthermore, it is estimated that 22% of people living in conflict regions have psychiatric disorders (Charlson et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…Studies have found that 10% of adolescents sought guidance from their teachers when faced with problems (Oban, 2011). Therefore, schools have become a consulting centers where students could get help safely (Kütük et al, 2016). Furthermore, it is estimated that 22% of people living in conflict regions have psychiatric disorders (Charlson et al, 2019).…”
Section: Introductionmentioning
confidence: 99%